Generalizability of Randomized Trials of the Programmed Intermittent Epidural Bolus Technique for Maintenance of Labor Analgesia: A Prospective Single-Centre Cohort Study. Issue 3 (September 2020) - Gabriel, L.; Young, J.; Hoesli, I.; Girard, T.; Dell-Kuster, S.
Abstract : ( Br J Anaesth . 2019;123:e434–e441) Neuraxial analgesia is the most widely used labor pain relief method, and patient-controlled epidural analgesia (PCEA) used in combination with a low-dose continuous epidural infusion has been shown to boost patient satisfaction while also increasing the volume of local anesthetics that are used. Researchers who have conducted randomized controlled trials (RCTs) have shown that substituting a programmed intermittent epidural bolus (PIEB) in place of PCEA can decrease local anesthetic consumption, but it is unclear if the maternal motor block in this method has a negative effect on labor progression. Because RCTs are almost always conducted on healthy nulliparous women, their results cannot easily be applied to the variety of patients seen in daily clinical practices. Gabriel and colleagues conducted their study on epidural labor analgesia data in order to compare the maternal motor function of RCT-eligible nulliparous women to parous women who are usually considered RCT-ineligible.